(untitled) (Journal of Engineering, 2025)
Over the past 10 years, there has been a surge in the study and implementation of smart city (SC) technology. A detailed analysis of the literature evaluations that have already been published on SCs reveals a deficiency of studies that categorize the literature into distinct themes and determine the most and least popular topics based on the number of peer-reviewed research papers that fall under each theme. In an attempt to close this gap, a descriptive literature evaluation of peer-reviewed papers on SCs has been carried out for this work. Over the past 10 years, there has been a surge in the study and implementation of smart city (SC) technology. Based on the number of peer-reviewed research articles that fall under each subject, a detailed analysis of the literature evaluations that have already been published on SCs reveals a lack of studies that classify the literature into different themes and identify the most and least popular topics. The investigation shows that although various frameworks provide insightful information, there is sometimes a lack of standardization, which complicates comparisons. Furthermore, the majority of frameworks fall short in addressing issues of social justice and public involvement in the assessment process. The study emphasizes the requirement for a single framework that guarantees inclusivity and integrates a variety of criteria.